PENGARUH CITRA MEREK TERHADAP NIAT PEMBELIAN TIKET PESAWAT SECARA ONLINE PADA KONSUMEN TRAVELOKA.COM DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI - Delsi Tuttia Rahmi, Ahmad Nizam (Departemen Manajemen, 2017)
This study aims to determine the influence of brand image towards the intention of purchasing airline tickets online on the costumers of traveloka.com, with trust as the mediating variable. The samples used in this research were 200 respondents who were users of traveloka.com website in order to purchase a plane ticket online in Banda Aceh. Purposive Sampling was used as sampling technique. The Hierarchical Linear Modeling (HLM) method was used as a method of analysis to determine the influence of the variables involved. The results of this study indicated that brand image significantly influences purchase intentions. In addition, the results showed that the variables of trust partially mediated the influence of brand image on purchase intentions. The better the brand image is given, the higher the consumer confidence is, thus the stronger the customer’s purchase intention would be.